Empowering Students to Serve Through the Manufacture of Organic Fertilizers at Islamic Boarding Schools - Imam Subqi; Saipullah Hasan; Nur Laily Fauziah (Prosperity: Journal of Society and Empowerment, 2022)
The purpose of the study was to explore (1) how the santri program and the steps of making organic fertilizers as well as the supporting and inhibiting factors using qualitative research methods. The results of this study indicate that: (1) the santri program that devotes life skills and develops nine business units owned by pesantren. (2) the step of making organic fertilizer begins with debriefing and subsequent implementation by preparing the ingredients to be put into a container, mixing the ingredients, stirring until mixed, putting the dough into a large drum tightly closed, waiting for 7 days, packing. (3) There are five supporting factors, namely (a) accompanied by people who have expertise, (b) having adequate facilities. (c) manufacture of independent decomposers as a way to minimize business costs and facilitate the materials needed in the manufacture of organic fertilizers. (d) cooperative relationship. (5) student commitment. While the inhibiting factors in the program of students who devote themselves are (1) the number of students is limited so that it greatly affects the running of the business unit. (2) there are still many students who prefer boyong from pesantren to seek life experiences. (3) Not able to manage properly, (4) there are still many students who are not interested